Gender and household decision-making in a Lao village: implications for livelihoods in hydropower development - Weeratunge, N.; Joffre, Olivier M.; Senaratna Sellamuttu, Sonali; Bouahom, B.; Keophoxay, Anousith (Informa UK Limited, 2016)
Hydropower development with concomitant changes in water and land regimes often results in livelihood transformation of affected people, entailing changes in intra-household decision-making upon which livelihood strategies are based. Economic factors underlying gender dimensions of household decision-making have been studied rigorously since the 1970s. However, empirical data on gender and decision-making within households, needed for evidence-based action, remain scarce. This is more so in hydropower contexts. This article explores gender and livelihood-related decision-making within rural households in the context of hydropower development in Lao PDR. Based on a social well-being conceptual approach with data from a household survey and qualitative interviews, it focuses on household decisions in an ethnic minority resettlement site soon after displacement, from an interpretive perspective. The article, first, aims to assess the extent to which household decision-making is gendered and secondly, to understand the complex reasoning behind household decisions, especially the relevance of material, relational, and subjective factors. It argues that while most household decisions are ostensibly considered as ‘joint’ in the study site, the nuanced nature of gendered values, norms, practices, relations, attitudes, and feelings underlying these decisions are important to assessing why households might or might not adopt livelihood interventions proposed by hydropower developers.